ANALISIS MODAL SOSIAL DALAM PROGRAM PEMBERDAYAAN MASYARAKAT DI DESA SUNGAI PINANG KECAMATAN TAMBANG KABUPATEN KAMPAR - Muslimah, Maratul; Yulida, Roza; Sayamar, Eri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims: analyze social capital in community development programs and to know the context of social capital in community development programs. This research uses a purposive sampling method with respondents consisting of 24 members of SPP PNPM Sungai Pinang. Data collection method in this research is primary data and secondary data. To determine the social capital in this research using a quantitative method using a questionnaire in the form of Likert Scale. From the research data showed that social capital in community development The results show that social capital in community development programs PNPM Mandiri is high with an average score 3.41 views from participation in networks, reciprocity, trust, social norms, values​​, and proactive action.Problems of social capital in community development programs is reciprocity, social norms, and actions that are proactive members. This is because most of the members of the SPP is still breaking the rules and less participate in group activities. Keywords: Community Empowerment Program, Social Capital